Antibacterial influences of accacia spp. in ed-duiem locality, White Nile province, Sudan. a chemical, pharmaceutical and traditional medicine overview - Rayan.Ali , Abdalla. (International Journal of Scientific World, 2025)
This study was focused on potential medicinal influences of the medium layer extracts of Accacia nilotica plants on inhibition of pathogenic aureus influences of Staphylococcus bacteria. Plant extracts were done to achieve water extracts with different concentrations. Chemical and physical tests were done to access the activity of; the former include [flavonoids, glycosides, sapiens, resins, phenols, alkaloids, and tannins], the latter include [pH and temperature] as potential affecters for Staphylococcus aureus bacteria. Samples were collected from patients in Ed-Duiem hospital, White Nile Province, Sudan. Study results significantly showed (p≤0.05) that Accacia spp. Extracts are effective bacterial inhibitors.